Islam and colonialism: becoming modern in Indonesia and Malaya - Ali, Muhamad (Edinburgh University Press, 2016)
This book offers a comparative and cross-cultural history of Islamic reform and European colonialism as both dependent and independent factors in shaping the multiple ways of becoming modern in Indonesia and Malaya during the first half of the twentieth century.